6.4.1 All for the Want of a Horseshoe Nail: An Examination of Causality in DoDAF/MODAF. Issue 1 (July 2014) - Hause, Matthew; Kihlström, Lars‐Olof
Abstract The title of the paper refers to the proverb of the death of Richard III of England at the Battle of Bosworth Field. "For want of a battle the kingdom was lost, … and all for the want of a horseshoe nail." The pattern described is called a chain of causality or causal sequence. DoDAF 2.0 contains many concepts that can document these sequences as well as the dynamic elements, feedback loops and influences. This paper will examine a telecommunications scenario and show how DoDAF is used to document and analyze the sequence. System Dynamics, Business Motivational Modeling (BMM), and simulation are also examined. System dynamics is an approach to understanding the behavior of complex systems over time. The Business Motivation Model (BMM) published by the OMG looks at ends, means, goals, and assessments. This will provide decision makers a more effective set of tools to evaluate operational scenarios as a means of improving outcomes. The method for how to attack a problem where causality needs to be revealed is also discussed.